2012
DOI: 10.1159/000334526
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Limbal-Conjunctival Autografting with Limbal Fixation Sutures after Pterygium Excision

Abstract: Purpose: To evaluate the efficacy and safety of limbal-conjunctival autografting with limbal fixation sutures after pterygium excision. Methods: We retrospectively reviewed the records of 90 patients (103 eyes) who received limbal-conjunctival autografts with limbal fixation sutures after excision of the primary pterygium (82 eyes) and recurrent pterygium (21 eyes). Results: The study subjects comprised 41 male patients (47 eyes) and 49 female patients (56 eyes) with a mean age of 51.1 ± 10.5 years (range 32–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
(62 reference statements)
0
4
0
1
Order By: Relevance
“…Furthermore, as for the use of amniotic membrane as an alternative to CAGs, Küçükerdönmez et al [12] did not yield any significant difference in recurrence rates in a prospective randomized clinical trial of 78 patients, and both Tananuvat and Martin [13 ]and Liang et al [14] demonstrated lower recurrent rates while using CAGs. With CAGs including the limbal areas, Han et al [15] and Torres et al [16] reported recurrence rates of 1.9 and 7.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as for the use of amniotic membrane as an alternative to CAGs, Küçükerdönmez et al [12] did not yield any significant difference in recurrence rates in a prospective randomized clinical trial of 78 patients, and both Tananuvat and Martin [13 ]and Liang et al [14] demonstrated lower recurrent rates while using CAGs. With CAGs including the limbal areas, Han et al [15] and Torres et al [16] reported recurrence rates of 1.9 and 7.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival and limbal-conjunctival grafts are described causes of pseudopterygium at the donor site [ 70 ]. Nevertheless, the incidence is low as reported in the literature as a result of the low amount of tissue that is necessary to be taken from the donor eye [ 71 ]. Han et al [ 71 ] studied the efficacy and safety limbal-conjunctival autografting with limbal fixation sutures after pterygium.…”
Section: Causes Of Pseudopterygiummentioning
confidence: 99%
“…Nevertheless, the incidence is low as reported in the literature as a result of the low amount of tissue that is necessary to be taken from the donor eye [ 71 ]. Han et al [ 71 ] studied the efficacy and safety limbal-conjunctival autografting with limbal fixation sutures after pterygium. A total of 90 patients with pterygium and recurrent pterygium were treated with this technique.…”
Section: Causes Of Pseudopterygiummentioning
confidence: 99%
“…12 외국의 연구에서 도 익상편 제거수술 후 자가 결막 및 윤부이식술 등의 수술 기법의 발달과 함께 익상편의 재발률이 3-17%로 감소하였 으나, 20 재발익상편의 경우 결막자가이식술을 시행한 경우 에도 재발률이 31-33%에 달하는 것으로 보고되고 있다. 21 Bianchi et al 22 은 익상편 조직의 면역화학염색을 통해 원 발익상편의 상피, 혈관내피 및 실질조직에서 혈관내피성장 인자(vascular endothelial growth factor; VEGF)의 발현이 정상 결막조직에 비해 증가하였음을 보고하였는데, 이는 VEGF가 혈관형성(angiogenesis)을 촉진하여 익상편의 증 식을 촉진할 수 있음을 시사한다.…”
unclassified